Fillers - Dong, Yu (John Wiley & Sons, Inc., 2012)
Fillers have played an important role in plastic and composite industries in aspects of traditional material reinforcements with higher modulus and strength, enhancements of multifunctional properties in thermal and/or electrical conductivities, heat distortion temperature, wear resistance and dimensional stability, and so on. Fillers synergistically act as essential constituent in composite materials to achieve many difficult-to-attain properties, which are the stringent requirements and specifications when employed for a wide range of end-user applications. The different types of fillers in terms of two major classifications of organic and inorganic fillers are elaborated in this article with special focuses on naturally extracted fillers for “green composites” and nanofillers for “polymer nanocomposites.” The filler processing methods are also explicitly reviewed, which are based on the conventional plastic molding techniques such as extrusion, injection molding, compression molding, thermoforming, blow molding, and rotational molding. Finally, the commonly used characterization techniques to deal with filler-reinforced composite materials are summarized in order to understand the processing-structure-property relationship due to the contribution of fillers in polymer matrices.